Correlation coefficient and path coefficient analysis studies in Brassica spp. for yield and quality traits: Correlation coefficient and path coefficient analysis studies in Brassica spp. for yield and quality traits - HITESH CHOUDHARY,; RAMESH,; RAHUL BHRADWAJ,; L NETAJIT SINGH,; MANISH KUMAR, (Journal of Oilseeds Research, 2023)
An experiment was conducted with 40 genotypes of Brassica species (Brassica juncea-15, Brasica rapa var. yellow sarson-10, Brassica rapa var. toria-5, Brassica tournefortii-5, Brassica nigra-2 and Brassica carinata-3) in Rabi season 2021-22 College of Agriculture, Jodhpur (Rajasthan). The experiment was put out in randomized block design (RBD) with 3 replications. Correlation coefficient analysis indicated that seed yield/plant had positive significant correlation with days to 50% flowering, days to maturity, plant height and siliqua density of main shoot. The direct effect on seed yield/plant were observed for plant height, number of primary branches/plant, first branch initiation height, number of seeds/siliqua, 1000 seed weight and glucosinolates. The genotypes MYS-172 and MN-2 showed high and low oil content, respectively, whereas, genotype TM309-1 and MBT-4 showed the highest and the lowest glucosinolates, respectively.